2016
DOI: 10.1039/c6ra11374e
|View full text |Cite
|
Sign up to set email alerts
|

Thiaporphyrin-mediated photocatalysis using red light

Abstract: Thiophene-containing porphyrin compounds are capable of catalytic, photo-reductive dehalogenation on an array of α-halo ketone model substrates with low catalyst loadings (0.1 mol%), in the presence of low energy, red light (>645 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
(12 reference statements)
0
22
0
Order By: Relevance
“…For instance, König and Zeitler demonstrated that a combination of eosin Y (OD13) with a sacrificial electron donor can trigger the reductive debromination of several α-carbonyl halides [53]. Riboflavin (OD11) [54] and thiaporphyrin [55] have been applied as well as organic photocatalysts for similar reductive dehalogenations.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, König and Zeitler demonstrated that a combination of eosin Y (OD13) with a sacrificial electron donor can trigger the reductive debromination of several α-carbonyl halides [53]. Riboflavin (OD11) [54] and thiaporphyrin [55] have been applied as well as organic photocatalysts for similar reductive dehalogenations.…”
Section: Methodsmentioning
confidence: 99%
“…Porphyrins containing other heteroatoms present physicochemical and electronic properties that are quite different from regular N 4 -porphyrins. These structures absorb and emit light at lower energies, as for example the thiaporphyrins that absorb beyond 650 nm [8,28]. Derksen and co-workers studied bond-cleavage reactions that can occur in biological microenvironments, using a light source with wavelengths frequently employed in photomedicine (650-850 nm) and thiophene-containing porphyrins [28].…”
Section: Review Porphyrins As Photoredox Catalystsmentioning
confidence: 99%
“…These structures absorb and emit light at lower energies, as for example the thiaporphyrins that absorb beyond 650 nm [8,28]. Derksen and co-workers studied bond-cleavage reactions that can occur in biological microenvironments, using a light source with wavelengths frequently employed in photomedicine (650-850 nm) and thiophene-containing porphyrins [28]. The authors reported that meso-5,10,15,20-tetraphenyl-21-monothiaporphyrin (STPP), combined with Hantzsch ester (HEH) and N,N-diisopropylethylamine (DIPEA), promoted the dehalogenation of α-functionalized carbonyl-containing compounds under red light (λ > 645 nm) in a reductive quenching.…”
Section: Review Porphyrins As Photoredox Catalystsmentioning
confidence: 99%
“…10 Later, the Derksen group introduced a red-light-induced photoreductive dehalogenation mediated by the thiaporphyrin 3b (Scheme 1b). 11 Afterwards, the Shibata group revealed a trifluoromethylation of alkenes and alkynes under red-light irradiation, mediated by the trifluoroethoxy-coated subphthalocyanine 3c (Scheme 1c). 12 Recently, in a related process, the Postigo group reported a fluoroalkylation reaction of (het)aromatics and sulfides with perfluoroalkyl iodides under red LED illumination employing zinc phthalocyanine dye (3d) as a PC (Scheme 1d).…”
Section: Red-light-induced Photocatalysismentioning
confidence: 99%